MENGAPA SHOPEE DAN TIKTOK MENJADI PLATFORM E-COMMERCE FAVORIT BELANJA SAAT INI DI SITUBONDO - Randika Fandiyanto; alif farhan romadhani; rik Ardiyanto; Gunawan Abdi Tauhid; Mohammad Nanda Rafliansyah (Growth, 2026)
The rapid development of digital technology and increasing internet accessibility have transformed consumer shopping behavior and accelerated the growth of e-commerce in Indonesia, including Situbondo Regency. Shopee and TikTok have emerged as two of the most preferred platforms due to their competitive prices, promotional strategies, technological features, convenience, and interactive shopping experiences. This study aims to identify and analyze the factors that make Shopee and TikTok the preferred e-commerce platforms among consumers in Situbondo, particularly in terms of promotions, price and incentives, shoppertainment, transaction convenience, content, and live commerce. This study employs a descriptive qualitative approach. Data were obtained through observations of e-commerce reports, relevant scientific literature, previous research, and supporting theories related to consumer behavior and digital marketing. The data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results indicate that promotions and competitive prices are the primary factors influencing consumer preferences for Shopee and TikTok. Shopee is more commonly preferred for routine purchases because of its relatively stable prices, promotional programs, and free-shipping incentives. Meanwhile, TikTok is more dominant in product discovery and impulsive purchasing through short-form videos, creator content, personalized recommendations, and live commerce. The shoppertainment concept provides consumers with an entertaining and interactive shopping experience that encourages product discovery and stimulates purchasing intentions. Ease of payment, transaction convenience, reliable logistics, and increasing digital literacy also contribute to e-commerce adoption in Situbondo. These findings suggest that local MSMEs and sellers should optimize promotional features, content marketing, and live commerce on both platforms to increase product visibility and sales